Author Correction: De novo phased assembly of the Vitis riparia grape genome - Girollet, Nabil; Rubio, Bernadette; Lopez-Roques, Céline; Valière, Sophie; Ollat, Nathalie; Bert, Pierre-François (Scientific data, 2019)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.An amendment to this paper has been published and can be accessed via a link at the top of the paper.